2024
DOI: 10.3847/1538-4357/ad19db
|View full text |Cite
|
Sign up to set email alerts
|

Powerful Radio-loud Quasars Are Triggered by Galaxy Mergers in the Cosmic Bright Ages

Peter Breiding,
Marco Chiaberge,
Erini Lambrides
et al.

Abstract: While supermassive black holes are ubiquitous features of galactic nuclei, only a small minority are observed during episodes of luminous accretion. The physical mechanism(s) driving the onset of fueling and ignition in these active galactic nuclei (AGN) are still largely unknown for many galaxies and AGN-selection criteria. Attention has focused on AGN triggering by means of major galaxy mergers gravitationally funneling gas toward the galactic center, with evidence both for and against this scenario. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 223 publications
0
0
0
Order By: Relevance
“…We emphasize important distinctions between our study and those focusing on the incidence of galaxy mergers in radioemitting systems. These studies (e.g., Chiaberge et al 2015;Breiding et al 2024) placed constraints on the merger fraction of AGN host galaxies; they began by selecting for a sample of luminous quasars and examined the host-galaxy morphology for signs of ongoing or recent gravitational interaction. Our sample, however, is of known merging galaxies that were selected because of their host-galaxy morphology and the presence of a single optical nucleus (C12).…”
Section: Prevalence Of Low-luminosity Radio Emissionmentioning
confidence: 99%
See 2 more Smart Citations
“…We emphasize important distinctions between our study and those focusing on the incidence of galaxy mergers in radioemitting systems. These studies (e.g., Chiaberge et al 2015;Breiding et al 2024) placed constraints on the merger fraction of AGN host galaxies; they began by selecting for a sample of luminous quasars and examined the host-galaxy morphology for signs of ongoing or recent gravitational interaction. Our sample, however, is of known merging galaxies that were selected because of their host-galaxy morphology and the presence of a single optical nucleus (C12).…”
Section: Prevalence Of Low-luminosity Radio Emissionmentioning
confidence: 99%
“…Observational studies are in conflict with one another over the role mergers play in triggering an AGN. While many have found either an increased AGN fraction in merging systems (Ellison et al 2011;Satyapal et al 2014;Donley et al 2018;Goulding et al 2018) or an increased merger fraction in AGN hosts (Chiaberge et al 2015;Fan et al 2016;Gao et al 2020;Marian et al 2020;Breiding et al 2024), others have found no such connection between AGNs and mergers (Grogin et al 2005;Cisternas et al 2011;Böhm et al 2013;Villforth et al 2017;Marian et al 2019;Lambrides et al 2021). Selection biases almost certainly contribute to this dissonance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation